2021
DOI: 10.1371/journal.pone.0261564
|View full text |Cite
|
Sign up to set email alerts
|

Course of lactate, pH and base excess for prediction of mortality in medical intensive care patients

Abstract: Introduction As base excess had shown superiority over lactate as a prognostic parameter in intensive care unit (ICU) surgical patients we aimed to evaluate course of lactate, base excess and pH for prediction of mortality of medical ICU patients. Materials and methods For lactate, pH and base excess, values at the admission to ICU, at 24 ± 4 hours, maximum or minimum in the first 24 hours and in 24–48 hours after admission were collected from all patients admitted to the Medical ICU of the University Hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…Furthermore, the results revealed that a higher APACHE II score, potassium levels, lactate levels, sodium levels, and respiratory rate; multiple organ support use and medication use; and older age as well as lower SPO2, MAP, platelet count, BMI, and O2 saturation were positively correlated with in-hospital death. The findings regarding the importance of variables are consistent with those of a previous study [ 7 , 11 , 12 , 32 , 33 , 34 ]. In this study, an inverse relationship was noted between diabetes mellitus and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the results revealed that a higher APACHE II score, potassium levels, lactate levels, sodium levels, and respiratory rate; multiple organ support use and medication use; and older age as well as lower SPO2, MAP, platelet count, BMI, and O2 saturation were positively correlated with in-hospital death. The findings regarding the importance of variables are consistent with those of a previous study [ 7 , 11 , 12 , 32 , 33 , 34 ]. In this study, an inverse relationship was noted between diabetes mellitus and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Statistical analysis was performed on the original datasets extracted from the NHANES and a complex sample analysis was performed using the stratification, cluster, and sample weight variables provides in the NHANES [ 56 ]. A new sample weight variable for the two combined datasets from 2011 to 2014 was created by taking one twice for the 2-year weight for each participant sampled from 2011 to 2012 and one twice for the 2-year weight for each person sampled from 2013 to 2014.…”
Section: Methodsmentioning
confidence: 99%
“…A direct comparison of our findings with other studies is problematic. Lactate and BE are routinely measured in critically ill patients suffering from various diseases, and both serve as mortality predictors in ICU (for example, in post-cardiac surgery patients or those with cardiogenic shock, ruptured abdominal aortic aneurysms, or trauma) [ 4 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Whether BE or lactate concentrations serve as better predictors of mortality in critical care patients has not yet been determined [ 4 , 33 , 34 , 35 , 36 ], with no studies reporting with certainty whether these predictors are both independent and/or additive.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schork et al reported a relationship between lactate, BE, and pH and mortality in 4067 intensive care unit patients [ 40 ]. The predicted mortality by SAPS II was 29%, and only 47% of them required mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation